Evidence of Interdomain Ammonium Cross-Feeding From Methylamine- and Glycine Betaine-Degrading Rhodobacteraceae to Diatoms as a Widespread Interaction in the Marine Phycosphere - Zecher, Karsten; Hayes, Kristiane Rebecca; Philipp, Bodo (Frontiers in Microbiology, 2020)
Dissolved organic nitrogen (DON) compounds such as methylamines (MAs) and glycine betaine (GBT) occur at detectable concentrations in marine habitats and are also produced and released by microalgae. For many marine bacteria, these DON compounds can serve as carbon, energy, and nitrogen sources, but microalgae usually cannot metabolize them. Interestingly though, it was previously shown that Donghicola sp. strain KarMa—a member of the marine Rhodobacteraceae—can cross-feed ammonium such that the ammonium it produces upon degrading monomethylamine (MMA) then serves as nitrogen source for the diatom Phaeodactylum tricornutum; thus, these organisms form a mutual metabolic interaction under photoautotrophic conditions. In the present study, we investigated whether this interaction plays a broader role in bacteria–diatom interactions in general. Results showed that cross-feeding between strain KarMa and P. tricornutum was also possible with di- and trimethylamine as well as with GBT. Further, cross-feeding of strain KarMa was also observed in cocultures with the diatoms Amphora coffeaeformis and Thalassiosira pseudonana with MMA as the sole nitrogen source. Regarding cross-feeding involving other Rhodobacteraceae strains, the in silico analysis of MA and GBT degradation pathways indicated that algae-associated Rhodobacteraceae-type strains likely interact with P. tricornutum in a similar manner as the strain KarMa does. For these types of strains (such as Celeribacter halophilus, Roseobacter denitrificans, Roseovarius indicus, Ruegeria pomeroyi, and Sulfitobacter noctilucicola), ammonium cross-feeding after methylamine degradation showed species-specific patterns, whereas bacterial GBT degradation always led to diatom growth. Overall, the degradation of DON compounds by the Rhodobacteraceae family and the subsequent cross-feeding of ammonium may represent a widespread, organism-specific, and regulated metabolic interaction for establishing and stabilizing associations with photoautotrophic diatoms in the oceans.